Supplier classification in emerging economies using the ELECTRE TRI-nC method: A case study considering sustainability aspects. (10th November 2018) - Costa, Ana Sara; Govindan, Kannan; Figueira, José Rui
Abstract: Resilience in the context of supply chains has received particular attention over recent years. Companies have been aware of the need to adopt resilience strategies in supply chain management. Therefore, considering resilience factors in the process of assessing and classifying suppliers (ordinal classification or sorting) is relevant. Supplier classification for further selection is a multiple criteria decision problem, which involves several criteria. In this paper, we adopt the ELECTRE TRI-nC method, which allows us to classify the suppliers taking into account multiple criteria and the decision makers' preferences, including resilience criteria. The method was applied to classify the suppliers of a manufacturing industry from an emerging economy (India). A sorting model was collaboratively constructed through an interaction process between the analysts and the decision makers (industrial managers). The proposed approach contributes to the decision process of selecting suppliers by providing a pre-classification of a set of suppliers into three different categories of overall performance. The results show that the proposed method is suitable and useful as a decision aiding tool for purchasing decisions, allowing managers to obtain robust conclusions. Highlights: Adoption of a multiple criteria approach to assess the performance of suppliers. Application of an outranking method, ELECTRE TRI-nC, to classify suppliers. Integration of resilience issues into the classification of suppliers. Real-world industry case in an emerging economy (India). Suitable method as a decision aiding tool for purchasing decisions.